Photolabile Ru Model Complexes with Chelating Diimine Ligands for Light‐Triggered Drug Release. Issue 13 (9th March 2018) - Battistin, Federica; Balducci, Gabriele; Wei, Jianhua; Renfrew, Anna K.; Alessio, Enzo
Abstract: Invited for the cover of this issue is the group of Enzo Alessio, University of Trieste, Italy, collaborating with the group of Anna Renfrew, University of Sydney, Australia. The cover image shows how a drug "chained" to an inert Ru complex can be photo‐released upon illumination. Abstract : The complexes described in this paper are a new entry in the field of photo‐activated ruthenium compounds… . Read more about the story behind the cover in the Cover Profile and about the research itself in theFull Paper by A. K. Renfrew, E. Alessio et al.